A Short Review on Application of Nanoemulsion for Enhanced Oil Recovery - Muhamad Afif Naqiudien Aladin; Hardyianto Vai Bahrun; Zykamilia Kamin; Zainal Zakaria; Awang Bono (2022)
Oil and gas industry contribute to a major energy resource in the world. Depletion of oil and gas reservoir has attracted researchers on the enhanced oil recovery (EOR) technique to extract the residual oil content in the reservoir after primary and secondary treatment. Since various techniques of EOR are available to be potentially applied, however, nanoemulsion extraction technique has gained attention for further exploration, owing to its favorable properties for EOR, especially in terms of its kinetic stability. Two methods for synthesizing nanoemulsion including low energy and high energy method were discussed. High energy method offers various advantages, mainly related to stability and amount of surfactant, which directly related to cost. Also, the different types of surfactants for nanoemulsion synthesis have been clearly distinguished and the mechanism of nanoemulsion flooding for the EOR has been briefly discussed. Lastly, the compilation of previous research on the application of nanoemulsion for EOR has been outlined.